TRAPP Complexes in Secretion and Autophagy - Kim, Jane J.; Lipatova, Zhanna; Segev, Nava (Frontiers in Cell and Developmental Biology, 2016)
TRAPP is a highly conserved modular multi-subunit protein complex. Originally identified as a “transport protein particle” with a role in endoplasmic reticulum-to-Golgi transport, its multiple subunits and their conservation from yeast to humans were characterized in the late 1990s. TRAPP attracted attention when it was shown to act as a Ypt/Rab GTPase nucleotide exchanger, GEF, in the 2000s. Currently, three TRAPP complexes are known in yeast, I, II, and III, and they regulate two different intracellular trafficking pathways: secretion and autophagy. Core TRAPP contains four small subunits that self assemble to a stable complex, which has a GEF activity on Ypt1. Another small subunit, Trs20/Sedlin, is an adaptor required for the association of core TRAPP with larger subunits to form TRAPP II and TRAPP III. Whereas the molecular structure of the core TRAPP complex is resolved, the architecture of the larger TRAPP complexes, including their existence as dimers and multimers, is less clear. In addition to its Ypt/Rab GEF activity, and thereby an indirect role in vesicle tethering through Ypt/Rabs, a direct role for TRAPP as a vesicle tether has been suggested. This idea is based on TRAPP interactions with vesicle coat components. While much of the basic information about TRAPP complexes comes from yeast, mutations in TRAPP subunits were connected to human disease. In this review we will summarize new information about TRAPP complexes, highlight new insights about their function and discuss current controversies and future perspectives.